2006
DOI: 10.1007/s00339-006-3579-z
|View full text |Cite
|
Sign up to set email alerts
|

Structural and optical properties of MgxAl1-xHy gradient thin films: a combinatorial approach

Abstract: The structural, optical and dc electrical properties of Mg x Al 1−x (0.2 ≤ x ≤ 0.9) gradient thin films covered with Pd/Mg are investigated before and after exposure to hydrogen. We use Hydrogenography, a novel high-throughput optical technique to map simultaneously all the hydride forming compositions and the kinetics thereof in the gradient thin film. Metallic Mg in the Mg x Al 1−x layer undergoes a metal-to-semiconductor transition and MgH 2 is formed for all Mg fractions x investigated. The presence of an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 47 publications
1
31
0
Order By: Relevance
“…With a straightforward optical setup, hydrogenography makes it possible to monitor hydrogen ab-and desorption simultaneously on thousands of samples under exactly the same experimental conditions. [8][9][10] We show here that hydrogenography is much more than a monitoring technique, as it also provides a high-throughput method to measure quantitatively the key thermodynamic properties (enthalpy and entropy) of hydride formation. We describe the essential ingredients of hydrogenography with the Mg-Ti-H system and demonstrate its combinatorial power with the Mg-Ti-Ni-H system.…”
mentioning
confidence: 97%
“…With a straightforward optical setup, hydrogenography makes it possible to monitor hydrogen ab-and desorption simultaneously on thousands of samples under exactly the same experimental conditions. [8][9][10] We show here that hydrogenography is much more than a monitoring technique, as it also provides a high-throughput method to measure quantitatively the key thermodynamic properties (enthalpy and entropy) of hydride formation. We describe the essential ingredients of hydrogenography with the Mg-Ti-H system and demonstrate its combinatorial power with the Mg-Ti-Ni-H system.…”
mentioning
confidence: 97%
“…326 Hydrogenography has also been utilized as a switchable mirror technology, taking advantage of the change in transmissivity that results from hydrogenation, as well as other applications. [327][328][329][330] Hydrogenography has been applied for compositional mapping of a number of Mg based systems such as Mg-Ni, 309,331 Mg-Ni-Ti, 332 Mg-Al, 333 and Mg-Al-Ti. 334 A notable result from this body of work was the discovery 316 of the alloy Mg 69 Ni 26 Ti 5 , Fig.…”
Section: Thin Film Combinatorial Workmentioning
confidence: 99%
“…The nanocrystalline MgH 2 shows improved kinetics with a desorption temperature that is about 100 K less compared to that of the untreated conventional powder. Recently, co-sputtering of Mg and Al has been used to destabilize the Mg matrix and create nanocrystalline or amorphous thin films [8,9]. Recent neutron reflectometry (NR) experiments on thin MgAl films [10] confirmed that Mg 0.7 Al 0.3 is the optimum composition to maximize the stored hydrogen content (4.1 wt%) and minimize the desorption temperature (448 K).…”
Section: Introductionmentioning
confidence: 99%